(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article explores the timeless influence of literature, tracing its historical evolution from oral traditions to contemporary digital narratives. It examines the various literary movements and their societal impacts, the role of literature in reflecting and shaping cultural identities, and its power as a catalyst for social change. The article also discusses the interdisciplinary nature of literature, its psychological insights, and its ability to foster global dialogue. Through these lenses, literature is highlighted as a vital force that preserves cultural heritage, enhances understanding, and inspires creativity and empathy in an increasingly interconnected world.